AN ERROR ANALYSIS ON RECOUNT TEXTS WRITTEN BY THE STUDENTS OF SMP NEGERI 6 MADIUN - Afendi, Agus Nur (2010)
In teaching learning English language, teachers in Junior High School used the best method. But during the learning process of English, the students find some difficulties and tend to make errors. Most of them make errors on tense. This study is aimed at (1) examining the type of English error by the second year students based on the linguistic term theorities and the surface strategy taxonomy of vocabulary and grammar (2) Examining the sources of English errors by second year students based on sources of error such as interlingual transfer and intralingual transfer. In this research, the researcher used descriptive qualitative research to analyze the data. This research was carried out at SMP Negeri 6 Madiun, especially in class VIII A and VIII B that consists of 40 students in 2009/2010 Academic Year. To collect the data, the researcher asked the students to write a paragraph which is a recount text. The study shows that the students made 292 errors in their works. Those errors are classified into seven kinds of error. The students made 22 errors in vocabulary which is in wrong spelling with frequency 7, 53%. The students made 106 errors in verb with frequency 36, 30%. Then in BE, the students made 52 errors with frequency 17, 81%. In modal auxiliaries, the students made 8 errors with frequency 2, 74%. In pronoun the students made 11 errors with frequency 3, 77%. In preposition, the students made 10 errors with frequency 3, 42%. And last in article, the students made 73 errors with frequency 25%. Those errors are mostly caused by interlingual transfer and intralingual transfer.